Percentage Analysis Of Knowledge And Use Of Fintech Products (Payment, Clearing, And Settlement) In Students (Case Study in Information & Business Information Darmajaya Bandar Lampung) - Atmaja I Made Dwiki; Maradona I Made Suteja; Diana Komang Tiara Setia (Prosiding International conference on Information Technology and Business (ICITB), 2022)
This study aims to provide an overview of the percentage of how well known fintech is among students, especially students of the Darmajaya Institute of Informatics and Business. The importance of the knowledge and ability of the younger generation towards fintech technology is a benchmark for the development of civilization. The presence of technology in the financial sector provides benefits to all users, especially students. However, it cannot be denied that the very rapid development of fintech makes fintech players also compete in getting customers. This study uses a descriptive quantitative method whose results are processed directly based on the results of the answers from the respondents. Respondents in this study were undergraduate and postgraduate students at the Bandar Lampung Institute of Information and Business. The results show that the percentage of students' knowledge of fintech is quite high, and the most popular fintech application in the payment sector among students is ShopeePay. The limitations of this study are not discussing the reasons for using fintech among students, so that the results of this study can be developed to provide benefits for human civilization, especially the scientific field of Financial Technology (fintech).                           Keywords: Fintech, Knowledge Aspect, Usage Aspect